Annual emission estimation comparison of two methods for a ship - Bilgili, L.; Celebi, U. B. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2015)
Ships can carry many kinds of goods with great capacities. They manage almost 90% of the world trade due to their capability to carry great amounts of goods. On the other hand, depending on the capacity, ship needs powerful engines and much more fuel than any other transportation way. Besides, fuel used by ships is one of the most unrefined by-products of oil. Thus, the air emissions of ships contents dangerous and harmful particles and compounds. These air emissions are especially dangerous for the people live in or near a port city that is close to the main shipping routes. The emissions include carbon monoxide (CO), carbon dioxide (CO2), Particulate Matter (PM), oxides of nitrogen (NOx) and oxides of sulfur (SOx). When a ship cruises between ports and berths at ports, it produces great amounts of these emissions. It is a very important issue to estimate the emissions to determine the emissions reduction methods. Based upon these kinds of calculations, worldwide total emissions could be estimated. In this paper we focus on one ship that works all over the world. The total air emissions have been estimated by the method offered by Trozzi, (2010). Both transit and docking modes are considered. The two estimation methods are compared: Fuel consumption approach and engine power approach. The differences between two methods are investigated.
Keywords: IMPACT; SYSTEM; CO2; Engineering